EXPLORING THE RELATIONSHIP BETWEEN SOCIAL MEDIA ENGAGEMENT, LIFESTYLE, COFFEE CULTURE TO CAFÉ VISIT INTENSITY AMONG STUDENTS - Sitorus, David Humala; Wasiman; Siagian, Mauli (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study investigates the relationship between Social Media Engagement, Lifestyle, and Coffee Culture on Café Visit Intensity among university students. Using a quantitative explanatory design, data were collected from 100 respondents at the University of Putera Batam and analyzed through multiple regression. The results reveal that Social Media Engagement and Coffee Culture significantly and positively influence Café Visit Intensity, whereas Lifestyle demonstrates no significant effect. Furthermore, the combined model indicates a statistically significant joint influence of all three variables on café visitation behavior. These findings contribute to the understanding of digital-mediated consumption among youth and highlight the importance of social and cultural factors in shaping students’ behavioral patterns toward café visitation in urban contexts.